Isolation, Screening, and Identification of Bacillus sp. Produced L- Glutaminase and Optimization of its Production by Submerged Fermentation - Hameed Abbood Jebur (Journal of Global Pharma Technology, 2018)
In this study L-glutaminase produced by locally Bacillus sp. isolated from different local of Iraqi soil. Fourteen isolates were selected to produce L-glutaminase by submerged fermentation. The isolate C13 showed a maximum L- glutaminase activity (28.08 U/ml). This isolate was identified according to morphological, cultural, Vitek 2 system and genetic analysis using 16srRNA gene. The microorganism was closely related to Bacillus subtilis according to gene bank database in NCBI, and signed as Bacillus subtilis MH049477.1. The L-glutaminase production pattern was studied under submerged fermentation and increased their yield after optimization of fermentation parameters. The highest L-glutaminase activity (61.12 U/ml) was achieved by using 3 % of galactose as the carbon source and 2% of yeast extract as nitrogen source at pH = 8, after 48 h of incubation at 37o C by using 2ml of inoculum contains 1x106 cfu /ml of Bacillus subtilis MH049477.1 . Fermentation was achieved in an incubator shaker at 120 rpm.Key words: Identification, Bacillus sp., L- glutaminase, Optimization, Submerged Fermentation